Dead in the water - Lynch, Chris, 1962- (Lynch, Chris, 1962- World War II, 2014)
After America is drawn into World War II, Hank McCallum finds himself on the USS Yorktown, an aircraft carrier in the Pacific, separated from his brother Theo, in constant danger from torpedoes, and just learning about the prejudice and segregation that plague his new friend from Tonga Bradford.